Peningkatan Peran Orang Tua terhadap Kemandirian Anak Berkebutuhan Khusus - Hudiyah Bil Haq, Aniq; Isqomah, Isqomah; Fakhriya Haq, Alfiza (Jurnal SOLMA, 2023)
Background: Parents and teachers certainly expect children with special needs to have independence in carrying out daily life. To increase independence, special programs are needed that aim to prepare children to become individuals who are ready to be part of society. Knowledge of parents and teachers about stimulation to build independence of children with special needs is still minimal, based on this background, a psychoeducation is made related to increasing the role of parents in the independence of children with special needs so that it is hoped that new knowledge about independence can help parents in nurturing, educating, and accompanying children with special needs to become independent children. Method: This activity was attended by 28 parents of students at SLB Untung Tuah. Psychoeducation was carried out with a lecture method that lasted for 90 minutes with a discussion about training the independence of children with special needs. Results: After psychoeducation, it is known that knowledge from parents is increasing about increasing children's independence, this is known through program evaluation. Conclusion: There is an increase in parental knowledge that is the target of activities regarding training the independence of children with special needs.